Flood risk perception among households in flood-prone areas of the Itang watershed, lower Baro Akobo Basin, southwest Ethiopia - Chengu, Shibiru; Assen, Mohammed; Gebeyehu, Elias (Frontiers in Environmental Science, 2025)
Flood risk perception plays a critical role in shaping household preparedness and response strategies. This study examines flood risk perceptions among vulnerable households in the Itang Watershed, Lower Baro-Akobo Basin, southwestern Ethiopia, and explores the socio-economic factors influencing these perceptions. Data were collected from 373 households across nine kebeles (smallest administrative unit, functioning as a local government structure) using a survey questionnaire, with binary logistic regression analysis. The results showed that prior flood experience made respondents 3.35 times more likely to perceive high flood risk (coefficient 3.353, p < 0.001), making this the strongest predictor in the study. Income was positively associated with flood risk perception (coefficient = 1.363, p = 0.001), indicating that wealthier individuals are more concerned about protecting their assets. Homeowners were less likely to perceive high flood risk compared to renters (coefficient = −1.664, p = 0.007), suggesting greater confidence or resources to mitigate flood risks. Employment status also had a substantial impact, with unemployed individuals significantly more likely to perceive high flood risk than employed ones (coefficient = −2.916, p < 0.001), underscoring the critical role of socio-economic conditions. Proximity to the river had a marginally significant effect (coefficient = 1.105, p = 0.053), with those living closer to the river perceiving slightly higher flood risk. Residents in lower watershed kebeles were more likely to perceive high flood risk compared to those in upper watershed kebeles (coefficient = −1.664, p = 0.072). However, age, household size, and education level were not significantly associated with flood risk perception. This study provides valuable insights for disaster management authorities to design region-specific flood risk preparedness and response strategies, eventually enhancing community resilience.